Relieving effect of an Maren-Zhizhu emulsion on loperamide hydrochloride-induced constipation in mice and its effects on the gut microbiota - Han, Xinran; Chai, Yuankun; Li, Na; Li, Chunyu; Yao, Fan; Huang, Qiang; Weng, Lili; Qiu, Zhidong; Jia, Ailing (Frontiers in Microbiology, 2025)
IntroductionConstipation, a common gastrointestinal disorder, is rapidly increasing in prevalence worldwide. An increasing number of individuals are choosing traditional Chinese medicine (TCM) as an adjunctive treatment for constipation. In this study, the effect of Maren-Zhizhu emulsion (MRZZ) prepared with Cannabis sativa L. (Huomaren), Rehmannia glutinosa Libosch. (Dihuang), Citrus aurantium L. (Zhiqiao), Atractylodes macrocephala Koidz. (Baizhu), and tiger nut oils from Cyperus esculentus L. on relieving loperamide hydrochloride-induced constipation in mice was evaluated.MethodsMRZZ was administered orally at low (0.65 g/kg) and high (2.6 g/kg) doses for 14 consecutive days. Loperamide hydrochloride (4 mg/kg) was used to induce constipation in male ICR mice. Colon tissue pathology, transcriptomics, and changes in the gut microbiota were analyzed to assess the efficacy of MRZZ in alleviating constipation.Results and discussionWe observed changes in fecal water content, time of first black stool, gastrointestinal transit rate, short-chain fatty acid (SCFAs) levels, and serum gastrointestinal regulatory peptide levels before and after consuming MRZZ. MRZZ increased the levels of relevant gastrointestinal regulatory neurotransmitters such as MTL, SP, and GAS, as well as SCFAs (especially acetate and isobutyrate). Furthermore, it reshaped the structure of the gut microbiota by increasing the relative abundance of Firmicutes and reducing potentially pathogenic bacteria, such as Proteobacteria. In addition, MRZZ suppressed intestinal inflammatory responses and enhances intestinal functions. In conclusion, MRZZ may alleviate constipation by synergistically regulating the gut microbiota, which may enhance the application value of TCM to treat constipation.